Child and adolescent psychiatry and the media - Beresin, Eugene V.; Olson, Cheryl K. (Elsevier, 2019)
Get a quick, expert overview of the increasingly important topic of technology and social media and its impact on children and adolescents. This practical resource presents a focused summary of today's current knowledge on topics of interest to psychiatrists, pediatricians, and other health professionals working with children and adolescents. It provides current, relevant information on a wide variety of media-related topics as they relate to child and adolescent health and mental illness, making it a one-stop resource for staying up to date in this critical area. - Resumé vydavatel